SIGNIFICANT RELATIONSHIP INTELLECTUAL CAPITAL AND MACRO ECONOMICS: A CASE STUDY - Subagyo, Ahmad; Wulandari, Siti Zulaikha; Saharuddin, Desmadi (International Journal of Research -GRANTHAALAYAH, 2020)
This paper aims to investigate the relationship between intellectual capital of several companies in Indonesia and macroeconomic variables Indonesia during the period 2011-2017 at 61 companies listed on the Stock Exchange. In this study using several intellectual capital variables in 61 companies and some Indonesian macro-economic variables are intellectual capital variable, Indonesian bank interest rate, consumer price index, producer price index, exchange rate index, inflation. This paper uses multiple regression data analysis techniques with OLS proposal model, linear difference and log analysis. From the results of studies that have been done can be explained that with the OLS regression model the relationship between several variable intellectual capital with some macroeconomic variables partially and simultaneously significant, as well as the difference. With log linear regression model analysis relationship between several variable intellectual capital with some macro economic variable simultaneously significant and partially between some variable intellectual capital significant and not significant partially with macro economic variable.